Clostridium Perfringens Enterotoxin (CPE) and CPE-Binding Domain (c-CPE) for the Detection and Treatment of Gynecologic Cancers - Jonathan D. Black; Salvatore Lopez; Emiliano Cocco; Carlton L. Schwab; Diana P. English; Alessandro D. Santin (Toxins, 2015)
Clostridium perfringens enterotoxin (CPE) is a three-domain polypeptide, which binds to Claudin-3 and Claudin-4 with high affinity. Because these receptors are highly differentially expressed in many human tumors, claudin-3 and claudin-4 may provide an efficient molecular tool to specifically identify and target biologically aggressive human cancer cells for CPE-specific binding and cytolysis. In this review we will discuss these surface proteins as targets for the detection and treatment of chemotherapy-resistant gynecologic malignancies overexpressing claudin-3 and -4 using CPE-based theranostic agents. We will also discuss the use of fluorescent c-CPE peptide in the operative setting for real time detection of micro-metastatic tumors during surgery and review the potential role of CPE in other medical applications.